Islamic Education Based on the Integration of Religious Character and Entrepreneurship in Islamic Boarding Schools - Ikbal, Muhammad; Arianto, Nanang; Arif, Marlian (Sekolah Tinggi Agam Islam Sumatera Medan, 2024)
Islamic boarding schools are unique Islamic educational institutions that have existed for more than a century. Their continuity is supported by their ability to innovate, as demonstrated by the Al-Junaidiyah Mandailing Natal Islamic Boarding School. One of its important innovations is the integration of entrepreneurial character alongside the strengthening of religious values. In this regard, this study aims to analyze the cultivation of religious and entrepreneurial character through integrated Islamic education. This study employs a qualitative research method based on case studies. Data collection includes interviews, observations, and document analysis. Data analysis is conducted using the Miles, Huberman, and Saldana model. The findings reveal that Al-Junaidiyah Islamic Boarding School not only focuses on deepening religious knowledge but also equips students with entrepreneurial values to enhance their competitiveness in society. These values are instilled through the strong commitment of the kyai and pesantren administrators. The planting methods used include integration-based learning, modeling, habituation, discipline, and a reward and punishment system. This study also develops Bourdieu's theory of cultural capital, emphasizing the importance of spiritual and dogmatic aspects in the process of internalizing religious values.